An empirical study of the 'underscreened' in organised cervical screening: experts focus on increasing opportunity as a way of reducing differences in screening rates. Issue 1 (December 2016) - Williams, Jane; Carter, Stacy
Abstract Background Cervical cancer disproportionately burdens disadvantaged women. Organised cervical screening aims to make cancer prevention available to all women in a population, yet screening uptake and cancer incidence and mortality are strongly correlated with socioeconomic status (SES). Reaching underscreened populations is a stated priority in many screening programs, usually with an emphasis on something like 'equity'. Equity is a poorly defined and understood concept. We aimed to explain experts' perspectives on how cervical screening programs might justifiably respond to 'the underscreened'. Methods This paper reports on a grounded theory study of cervical screening experts involved in program organisation. Participants were 23 experts from several countries and a range of backgrounds: gynecology; epidemiology; public health; pathology; general practice; policy making. Data were gathered via semi-structured interview and concepts developed through transcript coding and memo writing. Results Most experts expressed an intuitive commitment to reducing systematic differences in screening participation or cancer outcomes. They took three different implicit positions, however, on what made organised programs justifiable with respect to underscreened populations. These were: 1) accepting that population screening is likely to miss certain disenfranchised groups for practical and cultural reasons, and focusing on maximising mainstream reach; 2) identifying and removing barriers to screening; and 3) providing parallel tailored screening services that attended to different cultural needs. Positions tended to fall along country of practice lines. Conclusions Experts emphasised the provision of opportunity for underscreened populations to take up screening. A focus on opportunity appeared to rely on tacit premises not supported by evidence: that provision of meaningful opportunity leads to increased uptake, and that increased uptake of an initial screening test by disadvantaged populations would decrease cervical cancer incidence and mortality. There was little attention to anything other than the point of testing, or the difficulties disadvantaged women can have in accessing follow up care. The different approaches to 'improving equity' taken by participants are differently justified, and differently justifiable, but none attend directly to the broader conditions of disadvantage.